Utilization of Screening Mammograms in the Medicare Population Before and After the Affordable Care Act Implementation - Bozzi, Laura M.; Stuart, Bruce; Onukwugha, Eberechukwu; Tom, Sarah E. (Journal of aging and health, 2020)
Objective: This study examined screening mammograms in women aged 65 to 74 years and 75+ years before and after the Affordable Care Act (ACA) implementation. Method: This repeated cross-sectional study of community-dwelling women age 65+ years without a history of breast cancer or mastectomy utilized the Medicare Current Beneficiary Survey and Medicare fee-for-service claims data from 2001 to 2013. We used covariate-adjusted logistic regression with generalized estimating equations, stratified by age group. Results: The adjusted odds of screening mammograms in women aged 65-74 (n = 742) and 75+ years (n = 681) were lower in 2013 (odds ratio [OR]: 0.75, 95% confidence interval [CI]: [0.67, 0.83]; OR: 0.67, 95% CI: [0.60, 0.75], respectively) than the odds of screening mammograms in 2001. Discussion: Annual screening mammograms decreased in women aged 65 to 74 years and 75+ years, despite increased access from the ACA implementation. Future research as to why women are no longer receiving screening mammograms, such as changes in physician specialty guidelines, is warranted.